The development of a smart teacher book for preventing stereotypical behavior and suspicion in early childhood education - Agustin, Mubiar; Djoehaeni, Heny; Kamarubiani, Nike; Gustiana, Asep Deni; Pratama, Yoga Adi (Edelweiss Applied Science and Technology, 2024)
This research develops and assesses the effectiveness of the Smart Teacher Book in preventing stereotypical behavior and suspicion in early childhood education. Employing a mixed-method approach, it combines qualitative descriptive analysis by experts, practitioners, and book users with a quantitative assessment through quasi-experimentation to evaluate the book's effectiveness while being integrated into children's learning activities. Twenty early childhood education teachers participated and were evenly divided into experimental and control groups. The instruments consist of three scales: appropriate, less appropriate, and not appropriate. The book comprises two main sections. The first section is tailored for teachers, covering stereotypical behavior and suspicion and their causes, dangers, and prevention strategies. The second section is designed for children, presenting illustrated material addressing various stereotypes and suspicions related to social categories such as race, gender, religion, and politics. Meanwhile, the test results indicate that the Smart Teacher Book is effective for early childhood education teachers in mitigating stereotypical behavior and suspicion, as evidenced by the readability and effectiveness of the test results. Therefore, the book holds promise as a tool for fostering inclusivity and reducing prejudice in early childhood education settings.